Evaluation the health services quality in Al-Yarmok hospital using PubHosqual scale - Rasheed, Maysoon AbdulKareem Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aimed to know the level of health services quality in Al-Yarmouk Hospital, and also the level of indoor patients satisfaction, for this purpose we used (PubHosqal) measurement, which it applied in the first time in the Indian hospitals and then spreading in other countries. This instrument consist of (7) dimensions, that it involves (20) statements to measure the quality and (15) items as scale for patients satisfaction. Hobkins formule was used to determine the research sample that it was (171)persons .The (SPSS) program for social science used to analysis the primery data to obtain results that it refers to moderate level of health services quality and indoor patients satisfaction too . In the end researchers recomonded it is important to support the public hospitals by financing and carrying out behaviorural traning to phsicans, nurses and other employees to treatment indoor patients.